Better view by detachable string magnetically controlled capsule endoscopy for esophageal observation: a retrospective comparative study. Issue 4 (1st February 2020) - Song, J; Bai, T; Zhang, L; Xiang, X-L; Xie, X-P; Hou, X-H
SUMMARY: Magnetically controlled capsule endoscopy (MCE) system has been used to screen gastric lesions. However, the visualization performance of MCE in the esophagus has not been investigated systematically. String method improved the ability of capsule endoscopy (CE) for esophageal observing; however, the string attachment is complicated and cannot be detached with the CE inside the esophagus. We used a modified string, called detachable string attached to MCE. The aim of the study was to compare the observation performance of MCE with and without the detachable string. A total of 238 participants with upper gastrointestinal symptoms and a healthy check who refused esophagogastroduodenoscopy examination were retrospectively divided into the detachable string MCE group and the MCE alone group from June 2016 to May 2018. A suction cap with a thin, hollow string was attached to the MCE system in the detachable string group. Circumferential visualization of the esophagus including the upper, middle, and lower esophagus and Z-line, and esophageal focal lesion, as well as the recording time, safety and tolerability of the procedure, were assessed. The circumferential visualization of the upper, middle, and lower esophagus and Z-line was more efficient in the detachable string MCE group than in the MCE alone group ( P  < 0.001). In all, 31 esophageal lesions were detected in the detachable string MCE group, which was more than that in the MCE alone group (10, P  < 0.001). The mean recording time was 305 seconds in the string MCE group, which was longer than that in the MCE alone group (48.5 seconds, P  < 0.001). In seven participants (6.1%) in the detachable string MCE group, the capsule could not be separated from the string. Detachable string MCE showed better performance in terms of observation of the esophagus. Detachable string MCE can be used to screen for esophageal diseases as an alternative method in the future.